H3.Y discriminates between HIRA and DAXX chaperone complexes and reveals unexpected insights into human DAXX-H3.3-H4 binding and deposition requirements. Issue 10 (21st February 2017) - Zink, Lisa-Maria; Delbarre, Erwan; Eberl, H. Christian; Keilhauer, Eva C.; Bönisch, Clemens; Pünzeler, Sebastian; Bartkuhn, Marek; Collas, Philippe; Mann, Matthias; Hake, Sandra B.
Abstract: Histone chaperones prevent promiscuous histone interactions before chromatin assembly. They guarantee faithful deposition of canonical histones and functionally specialized histone variants into chromatin in a spatial- and temporally-restricted manner. Here, we identify the binding partners of the primate-specific and H3.3-related histone variant H3.Y using several quantitative mass spectrometry approaches, and biochemical and cell biological assays. We find the HIRA, but not the DAXX/ATRX, complex to recognize H3.Y, explaining its presence in transcriptionally active euchromatic regions. Accordingly, H3.Y nucleosomes are enriched in the transcription-promoting FACT complex and depleted of repressive post-translational histone modifications. H3.Y mutational gain-of-function screens reveal an unexpected combinatorial amino acid sequence requirement for histone H3.3 interaction with DAXX but not HIRA, and for H3.3 recruitment to PML nuclear bodies. We demonstrate the importance and necessity of specific H3.3 core and C-terminal amino acids in discriminating between distinct chaperone complexes. Further, chromatin immunoprecipitation sequencing experiments reveal that in contrast to euchromatic HIRA-dependent deposition sites, human DAXX/ATRX-dependent regions of histone H3 variant incorporation are enriched in heterochromatic H3K9me3 and simple repeat sequences. These data demonstrate that H3.Y's unique amino acids allow a functional distinction between HIRA and DAXX binding and its consequent deposition into open chromatin.